2020
DOI: 10.1111/cyt.12935
|View full text |Cite
|
Sign up to set email alerts
|

The utility of fine needle aspiration cytology in orbital haematolymphoid neoplasms

Abstract: Background Orbital hematolymphoid lesions are rare and usually encountered in elderly patients. Orbital lesions are not easy to biopsy: hence fine needle aspiration cytology (FNAC) can be a very good diagnostic modality for these lesions. Materials and Methods Cases of orbital masses subjected to FNAC dating from 2013 to 2020 were retrieved from our archives. A total of 16 cases with biopsy confirmation were included. All clinical details, the type of procedure, details of the immunocytochemistry (ICC) perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…They also reported 100% sensitivity and 87% specificity among all lesions studied 108 . Other authors showed that 75% of orbital haematolymphoid neoplasms were accurately diagnosed by cytology 109 . Interestingly, our review detected that 26.6% of the additional cases were misdiagnosed (i.e., inconclusive results or a diagnosis other than PCN).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…They also reported 100% sensitivity and 87% specificity among all lesions studied 108 . Other authors showed that 75% of orbital haematolymphoid neoplasms were accurately diagnosed by cytology 109 . Interestingly, our review detected that 26.6% of the additional cases were misdiagnosed (i.e., inconclusive results or a diagnosis other than PCN).…”
Section: Discussionsupporting
confidence: 53%
“…108 Other authors showed that 75% of orbital haematolymphoid neoplasms were accurately diagnosed by cytology. 109 Interestingly, our review detected that 26.6% of the additional cases were misdiagnosed (i.e., inconclusive results or a diagnosis other than PCN). These discrepancies, however, were identified as PCN in a subsequent biopsy.…”
Section: Demographic Data and Clinical Featuresmentioning
confidence: 85%
See 1 more Smart Citation
“…Stephen et al 7 explored fine needle aspiration cytology (FNAC) for diagnosing orbital lymphoid tissue tumors. FNAC, being a minimally invasive and effective method, provides essential cytological diagnostic information for orbital lymphoid tissue tumors, particularly malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…MS is a highly aggressive disease and shows a poor complete response rate after standard chemotherapy [14]; however, the grim survival of this disease can be decelerated to some extent with timely initiation of appropriate therapy that is contingent upon a prompt, accurate, and complete diagnosis. The morphologic features of MS in cytologic preparations such as FNA smears, touch preparations (TPs), and ThinPrep have been reported only sporadically in the literature, and the majority of the published data come from single case reports or small case series [15][16][17][18][19][20][21]. Failure to recognize MS in cytologic specimens combined with the aforementioned complexities associated with this diagnosis may delay or even misdiagnose this dismal disease.…”
Section: Introductionmentioning
confidence: 99%